2020
DOI: 10.1515/ijamh-2019-0069
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of unintentional injuries and socio-psychological correlates among school-going adolescents in Timor-Leste

Abstract: AbstractObjectivesThe study aimed to report on the prevalence and socio-psychological correlates of non-fatal injury among school-going adolescents in Timor-Leste.MethodsCross-sectional data from the 2015 Timor-Leste “Global School-based Health Survey (GSHS)” includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…In the current study, the most reported causes of serious injuries were; fall, hit by an object or something, and motor vehicle accidents, while the majority reported cut or stab wound, a broken bone or dislocated joint, and head injury or concussion as the frequent type of serious injury. Similar findings have been reported in other GSHS studies [ 13 , 15 , 20 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the current study, the most reported causes of serious injuries were; fall, hit by an object or something, and motor vehicle accidents, while the majority reported cut or stab wound, a broken bone or dislocated joint, and head injury or concussion as the frequent type of serious injury. Similar findings have been reported in other GSHS studies [ 13 , 15 , 20 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…All the studies reported prevalence rates below fifty percent. However, higher rates were found in Egypt (68.5%) [ 33 ] Djibouti (61.1%) [ 2 ], 65.8% in Botswana [ 16 ], and 70% in Timor-Leste [ 24 ]. Additionally, our finding on the prevalence of unintended injuries was lower compared to that of Pelzter [ 14 ], who reported a 68.2% prevalence of one or multiple injuries among adolescents from six African countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7-9,28-30 Notably, mental health is a risk factor for non-fatal injuries among female students and for violence in both genders, which accords with previous studies. 29,31 With the popularity of social platforms and rapid access to a wide range of information, Vietnamese students may face an increased risk of mental health problems, which is particularly worrying given that mental health is also associated with violence and non-fatal injury. Moreover, parents were found to play a crucial role in preventing violence and non-fatal injury among Vietnamese students; this may be explained by Vietnamese family culture, where parents and children have close bonds, and parents are often involved in children’s education, personal development, and even daily activities.…”
Section: Discussionmentioning
confidence: 99%